Developing a construction industry web-based learning system in construction management education - Toh, Tien Choon (2006)
This research is dealing with the development of a web-based learning system for the post graduate candidates and the short courses participants in order to provide a medium, in learning and gaining knowledge in the field of construction management. The computer enhanced training and e-learning approaches are used to assist in the education of construction management especially in fighting the attack of viruses in the Universiti Teknologi Malaysia (UTM) campus recently. Thus, the integration between the newly developed e-learning with the Construction Technology and Management Centre (CTMC) existing web portal is essential. Hence, the first objective of the study is to identify the current state of the art regarding the types of teaching methods in the field of Construction Management studies. Secondly, the research is also intended to identify the information regarding the current syllabuses of the Master of Science in Construction Management education and suitable materials for the short courses. Eventually, a web-based learning system for the post graduate candidates in construction management program and the short courses participants is developed by utilizing the Dokeos open source e-learning software. The research methodologies used include the knowledge acquisition technique, documentary analysis and the web portal development model. This research will be directly focused on the Construction Technology and Management Centre (CTMC) needs through a problem solving basis. It is believed that the developed e-learning web portal, therefore, is an approach to facilitate and enhance learning for personnel involved in construction through computer and communication technology.